Trajetórias políticas e o perfil das vereanças em Sorocaba/SP. - Tomoto, Thiago Hideo (Universidade Federal de São Carlos, 2026)
Analyzing institutional politics in Brazil requires an examination of its past as a means to understand the present and envision possibilities for "other futures." It is fundamental, therefore, to recover the profiles of representatives who have occupied decision-making spaces and to identify the interests and objectives that permeated the sphere of institutional political representation. Consequently, understanding the profiles of city councillors (vereadores) in Sorocaba/SP, within a timeframe beginning in 1948, constitutes the central object of this thesis, which seeks clues to understand institutional political dynamics.The focus on Sorocaba’s local legislature is configured not merely as a research possibility, but as a recovery of the author's own political trajectory within the city. This lived experience becomes an investigative tool intertwined with scientific research, structured under rigorous sociodemographic analysis, fieldwork, and theoretical foundation. Thus, examining the locality from this perspective serves as a strategy to identify potential generalizations that assist in understanding electoral dynamics at state, national, and global levels. The recovery of these dynamics at the territorial level allows for an understanding of the vestiges of the roots that forge the relations between representatives and the represented. The identification of phenomena such as coronelismo (colonelism), mandonismo (bossism), and clientelism - and their developments through the lenses of the "legislator," the "procurer," and the "welfare provider" - comprises the framework chosen by the author to categorize, based on semi-structured interviews, the councillors elected for the first time in the 2024 elections. Furthermore, this study seeks to demonstrate how this modus operandi perpetuates itself, alongside the hypothesis of an emerging new group, termed by the author as the "personalist" group. This profile does not necessarily maintain a bond with the territory, a party project, or a political party; rather, it fosters a direct identification with the voter through themes that transcend local jurisdiction and the traditional role of the councillor, mediated primarily by social networks. Finally, the study reflects upon the profiles of councillors in Sorocaba/SP, emphasizing variables such as gender, race, religion, and marital status, in search of investigative evidence on how these new profiles may reorganize the dynamics of institutional politics.
Trayectorias políticas y el perfil de las concejalías en Sorocaba/SP.
Political trajectories and the profile of city councillorships in Sorocaba/SP.
Keywords: Representação política; Eleições; Personalista; Vereadores; Sorocaba/SP; Political representation; Elections; Personalist; City councillors; Sorocaba/SP; CIENCIAS HUMANAS; 16. Paz, Justiça e Instituições Eficazes